MEMPROGRAMKAN PENGENALAN MANAJEMEN WAKAF DI DESA PURASEDA, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Ermi Suryani; Bayu Purnama Putra; Hilal Fadhilah Kautsar (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
This community service aims to introduce waqf management in Puraseda Village, Leuwiliang District, Bogor Regency. Thus, the subject of community service is the people of Puraseda Village, Leuwiliang District, Bogor Regency. In this community service, activities are carried out that provide knowledge about waqf management, so that the community understands and is able to organize existing resources to carry out waqf management well